Developing a multi-areas model in strategic thinking (Departments in private banking, health and education sectors) - السعيدي, يعرب عدنان; رحيم, رائد غانم (Journal of Economics and Administrative Sciences, 2016)
AbstractThe study discussed three areas in strategic thinking, namely, (patterns elements, outcomes) , this study aimed to measure extent to which strategic leaders have the type or types of patterns of strategic thinking, and measure the extent of their use of the elements of strategic thinking, and measurement of strategic thinking outcomes for managers at various levels , And to know the relationship between the modes of strategic thinking, elements and outcomes in organizations. the study included five banks and four hospitals and four colleges and universities, has been a research sample consisted of 168 individuals, distributed in positions (Director General , Director of Directorate , Director of Department, Director of the Division) , To achieve the objectives of the research , researcher used hypothesis testing and correlation analysis and regression, it has led to results : Rejection of the original hypotheses and search for alternative        hypotheses to study the relationships between the components of the model, the most important finding is the patterns representing independent individual trends has specific characteristics, and thus the nature of the interaction between the components of strategic thinking occur on the basis of the characteristics of a pattern. Therefor each pattern was effective in some components and relate in negative relation with another components. And show us owning a pattern of strategic thinking (synthetic - abstract) by members of the community study as  a whole more than other types, owning pattern (synthetic - concrete) by (health sector) to being a competent one thing in most of his works, the pattern (synthetic - abstract) by (the banking sector) to being a contend with several issues at the same time, the pattern (analytical - abstract) by (education sector).Use the (Systemic perspective) by (health sector) and that integration and comprehensive work in the departments of hospitals, and the element of (Intelligent Opportunism) by (the banking sector) because it deals with money of others and needs to the profits always and liquidity, and the element of (Intelligent Opportunism) by (education Sector) so as to obtain the feature makes it superior to others. It was strategic thinking on the (level of organizational outcome) greater than the thinking at the (individual level) , and the presence of outcome showing the (organizational level) by (health sector) because the private sector is seeking to benefit from the expertise and strengthened through strategic dialogues, and the (Organizational level) by (banking sector) to the fact that an integrated collective work here, and the (individual level) by (education sector) to the fact that most individuals rely on personal knowledge and experience.